1999
DOI: 10.1007/s007010050330
|View full text |Cite
|
Sign up to set email alerts
|

Neurovascular Compression Syndrome of the Eighth Cranial Nerve. Can the Site of Compression Explain the Symptoms?

Abstract: Considerable skepticism still exists concerning the concept of neurovascular compression (NVC) syndromes of the eighth cranial nerve (8th N). If such syndromes exist, the sites of compression of the nerve must explain the symptoms encountered. We recorded compound action potentials of the cochlear nerve (CCAPs) during neurovascular decompression (NVD) to examine the topography of the three components of the 8th N. The sites of compression of the 8th N in cases of NVC syndrome confirmed at surgery were superimp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
12

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 8 publications
4
37
0
12
Order By: Relevance
“…Naqueles com vertigem e sintomas auditivos a compressão ocorre nas porções caudal e ventral do VIII nervo. Nos pacientes com sintomas v e s t i b u l a res, com ou sem sintomas auditivos, associados a sinais de comprometimento de outros nervos cranianos há compressão vascular dos nerv o s adjacentes na fossa posterior (V e VII nervos cranianos) 6 .…”
Section: Discussionunclassified
“…Naqueles com vertigem e sintomas auditivos a compressão ocorre nas porções caudal e ventral do VIII nervo. Nos pacientes com sintomas v e s t i b u l a res, com ou sem sintomas auditivos, associados a sinais de comprometimento de outros nervos cranianos há compressão vascular dos nerv o s adjacentes na fossa posterior (V e VII nervos cranianos) 6 .…”
Section: Discussionunclassified
“…In contrast to the clearly established NVCS of CN V and VII, NVCS of CN VIII is more controversial. 55 The site of NVC can vary between 0.0 and 10.2 mm from the brain stem, and in most cases (75%), the AICA is the compressing vessel. 56 The recording of action potentials of the cochlear nerve during microvascular decompression has demonstrated that the site of NVC correlates well with clinical symptoms.…”
Section: Vestibulocochlear Nerve (Cn Viii)mentioning
confidence: 99%
“…56 The recording of action potentials of the cochlear nerve during microvascular decompression has demonstrated that the site of NVC correlates well with clinical symptoms. 55 Ryu et al 55 have shown that vertigo appears to be associated with vascular compression of the rostroventral nerve (vestibular nerve), while tinnitus appears to be associated with compression of the caudal surface (cochlear nerve) of the nerve (Fig 9). In patients with both vertigo and tinnitus, the authors found compression of both the vestibular and cochlear nerves.…”
Section: Vestibulocochlear Nerve (Cn Viii)mentioning
confidence: 99%
“…Generalno u populaciji, kontakt između n. VIII i vaskularne omče otkriven na CT cisternografiji kao normalan anatomski nalaz, nalazi u 7% do 12% na anatomskim disekcijama i 14% do 34% na MRI [10]. Ryu i saradnici [23] imaju suprotno mišljenje i smatraju da potvrda postojanja ovog sindroma može objasniti simptome koje susrećemo i da zavise od dijela nerva na koji je izvršena kompresija od strane krvnog suda. Nađeni su i slučajevi kada izražena horizontalna petlja intrakranijalnog dijela lijeve a. vertebralis oko n.VIII, koja je bila u bliskom kontaktu s otvorom unutrašnjeg slušnog kanala uzrokuje unilateralno smanjenje sluha (sindrom kohleo-vertebralne zamke) [24].…”
Section: Diskusijaunclassified